An Overview on SDN Architectures with Multiple Controllers - Othmane Blial; Mouad Ben Mamoun; Redouane Benaini (Journal of Computer Networks and Communications)
Software-defined networking offers several benefits for networking by separating the control plane from the data plane. However, networks’ scalability, reliability, and availability remain as a big issue. Accordingly, multicontroller architectures are important for SDN-enabled networks. This paper gives a comprehensive overview of SDN multicontroller architectures. It presents SDN and its main instantiation OpenFlow. Then, it explains in detail the differences between multiple types of multicontroller architectures, like the distribution method and the communication system. Furthermore, it provides already implemented and under research examples of multicontroller architectures by describing their design, their communication process, and their performance results.